Czas a tożsamość w perspektywie kulturowej — na przykładzie powieści Lisy See „ Kwiat Śniegu i sekretny wachlarz ” - Brzozowska, Dorota (Stylistyka, 2021)
The aim of the paper is to show the relationship between different aspects of time and the way they are built in the construction of a narrator’s identity. To highlight the cultural specific dimension of identity a book describing life in ninetieth century China has been chosen. The main heroine ofLisa Sees’s novel Snów Flower and the Secret Fan Lily is telling her life story and presents in a detailed way certain roles she has taken and the things she has had to suffer from (among them the painful footbinding) before she became who she is. The relationship between her and her laotong ‘the same’ is the core of the novel and is also vital for Lily’s self-identification. The ways in which the identity is con- structed out of cultural bound details is shown altogether with the features that make it universal no matter which culture representative they concem. The ąuestion of various types of womanhood is also vital for the paper. The elementary units proposed by Wierzbicka in relation to time are taken into consideration to describe the portrait of the novel’s heroine. The results of the analysis show that the category of NOW is of the greatest im- portance as far as identity issues are concemed.